Prevalence and associated factors of intimate partner violence (IPV) against women in Bangladesh amid COVID-19 pandemic - Istihak Rayhan; Khaleda Akter (Heliyon, 2021)
Background: Intimate Partner Violence (IPV) is a serious violation of women's human rights and a dominant chronic global public health problem. Although it is suspected that epidemic-induced economic downturns have fueled the IPV, enough empirical literature are not available to make a consensus. Against this backdrop, the present study has attempted to explore the prevalence and associated factors of IPV amid the COVID-19 pandemic. Methods: The study has included Bangladesh as the study area and collected data from married women who lived with her intimate partner. Total of 605 women were reached and 84.30% (510) women, aged 16–45 with mean age 30.12 (±6.27) years, provided their consent and required information. The study has employed the translated version of WHO multi-country study tools to screen the IPV. Results: This cross-sectional study has found the prevalence of IPV about 45.29%, where 44.12% are emotionally abused, 15.29% physically, 10.59% sexually, and 19.22% are abused either physically or sexually. The study has found that types of marriage, area of residence, women's employment status, husband's age and level of education, family income status, and pandemic induced economic downturns were the associated factors of intimate partner violence amid the pandemic. Limitations: Self-reported cross-sectional study has some methodological limitations, and the present study is not free from them. Conclusions: The study contributes to the existing literature by highlighting the associated factors of IPV amid the pandemic, which will help to make preventive policy.